2014
DOI: 10.5152/tjg.2014.4231
|View full text |Cite
|
Sign up to set email alerts
|

Acute liver failure in Turkey: A systematic review

Abstract: Background/Aims: To present the causes of acute liver failure in Turkey. Materials and Methods: International and national medical research databanks were searched for publications related to acute liver failure and originating from Turkey. Patients in the databank of acute liver failure of our center were also added to this literature search. Patients were evaluated for age, gender, etiology, treatment modality, and outcomes. Results: A total of 308 patients were analyzed. Hepatitis A (20.9%) for children and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 25 publications
(5 reference statements)
1
18
0
5
Order By: Relevance
“…The most common cause of this disease is viral hepatitis developing into fulminant hepatitis; among these cases, the most frequently seen microorganisms are HAV in children and HBV in adults (17). Fulminant hepatitis develops at a prevalence rate of 0.1% to 0.4% in acute HBV cases (18).…”
Section: Discussionmentioning
confidence: 99%
“…The most common cause of this disease is viral hepatitis developing into fulminant hepatitis; among these cases, the most frequently seen microorganisms are HAV in children and HBV in adults (17). Fulminant hepatitis develops at a prevalence rate of 0.1% to 0.4% in acute HBV cases (18).…”
Section: Discussionmentioning
confidence: 99%
“…Mushroom poisoning was the most common toxic cause of ALF in our study. A systematic review reported that mushroom intoxication was the most frequent factor of toxic liver failure for both adults and children (13%) in Turkey (9). This can lead to ALF with high mortality, which is likely due to late presentation (27).…”
Section: Original Articlementioning
confidence: 99%
“…However, the cause of ALF still remains undetermined in a large proportion of children (5). Some centers with and without liver transplantation (LT) facilities in Turkey have reported their experience of the etiology of ALF in childhood (6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…1,5,6 As causas variam consoante a idade e área geográfica ou nível Revista Científica da Ordem dos Médicos www.actamedicaportuguesa.com Jerónimo M, et al Referenciação precoce na falência hepática aguda pediátrica, Acta Med Port 2015 Sep-Oct;28(5):559-566 socioeconómico da região. 2,5,7 O seu tratamento constitui um desafio para os profissionais de saúde. Combina a abordagem inicial de uma doença rapidamente progressiva com envolvimento multiorgânico e a necessidade urgente de decidir manter apenas a terapêutica médica de suporte ou avançar para um transplante hepático (TRH) urgente.…”
Section: Introductionunclassified